Creating value-added sisal processing products of the Hupkaphong community, Cha-am district, Phetchaburi province - Yeesoontes, Watchara; Tunphan, Aing-on (Journal of Management Science Nakhon Pathom Rajabhat University, 2019)
The objective of this research is to develop sisal products of the agricultural cooperative village of Hupkaphong. Product To be soft and can be waterproof then test the opinions of consumers on new sisal product development. The research process begins with the development of products that are soft, using the process of soaking the hemp fibers with 1 hour of potassium hydroxide and dyeing as needed. Then soaked with 0.5 molar acetic acid for 3 hours and then put the hemp fibers to be the product. Then create a waterproof ability by spraying with fluorocarbon. And then used to test the opinions of the consumers on new sisal products of the village agricultural cooperatives Hupkapong In terms of newly developed products. The statistics used in data analysis, consisted of percentage (mean) and mean (Mean) and standard deviation (Standard Deviation) to describe demographic data and Pearson Chi-Square ( P) to explain the relationship and Paired Simples T-Test to compare the mean and the relationship between variables. The results of the research on personal factors are related to the number of purchases of new sisal products. Gender, age, education level The monthly income and the different occupations are different in relation to the number of purchases of new sisal products. Issues of pre-purchase expectations and the satisfaction after the purchase of new sisal products are different. In the quality of good raw materials The product is durable. The beauty of modern design continuous model development when used, it is safe and good image of the product. Article history : Received 25 December 2018 Revised 16 February 2019 Accepted 18 February 2019 SIMILARITY INDEX = 2.54